Perbandingan Analisis Usability Aplikasi Marketplace Pertanian Menggunakan Metode Usability Testing dan User Experience Questionnaire - Eva Proditus Sianturi; Miftahul Jannah (Jurnal ICT: Information Communication & Technology, 2022)
Marketplace engaged in the agricultural sector has a role as a direct liaison between farmers and consumers as well as answers to problems faced by farmers in terms of distribution of agricultural products. Several reviews on the Google Play Store from marketplace application users assessed that the process of ordering goods in the Sayurbox and Segari applications was less effective and efficient. This study aims to compare the convenience, perception and user experience obtained when using the Sayurbox and Segari applications which have the same business characteristics in usability. The comparison method uses usability testing through task scenarios to obtain aspects of usability measurement, namely effectiveness, efficiency for 5 respondents. After that, interviews were conducted to find out more detailed usability problems while the user satisfaction aspect used the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) questionnaires which were distributed to 50 respondents online via Google form. The results showed positive perceptions of respondents to the Segari application with an average value of > 0.8 which is the limit of the normal result value and has the highest value for each parameter compared to the Sayurbox application. This shows that the Segari application has a better reception, ease, and perception or user experience.